Community Knowledge, Attitude and Practices towards Tuberculosis among Household Heads in Mogadishu, Somalia - Yusuf - Isleged, Mohamed (Integrated Journal for Research in Arts and Humanities, 2022)
Tuberculosis (TB) is a disease that reappears after they have been on a significant decline occurring worldwide and a source of multi-billion- dollar loss and human fatality yearly. The situation is worse in developing countries like Somalia, where lower knowledge, attitude, and practice (KAP) of the people is impending. A cross sectional survey was conducted between January 2022 and June 2022 to assess the knowledge, attitude and practices towards tuberculosis among 171 household heads in Wadajir district Mogadishu, Somalia. A structured questionnaire was designed, pretested and self-administered to household heads. Human TB was recognized by 157(91.8 %) of household heads, while only 34(19.9%) had heard of animal TB. In the present study, 121(70.8%) of household heads had not considered bovine Tb as zoonosis. Majorities of respondents indicated that they have acquired the awareness about TB from Family/neighbors that accounts for about 80(46.8%), and only 38(22.2%) of them got information from radio/TV. Knowledge on the infectious cause of human and animal TB was known by 4.7%. However, misperceptions such as weather and toxins were also implicated as causes of human TB. In the present study, a significant proportion (48.5%) of the study population used to consume raw milk that was studied as the sources of infection to TB. Herein, the majority of household heads have indicated inhalation (57.3%) and contacts (23.4%) as means of transmission of human tuberculosis and only (15.7%) of respondents mentioned consuming raw animal products. In conclusion, as the bovine tuberculosis is less aware as well as misperception about cause, ways of transmission and prevention towards human tuberculosis on household heads. Thus, it is highly necessary to convey public health education to assemble public awareness about the transmission, etiology, predisposing factors of infection and its prevention and control in the study area.